(untitled) (Bangladesh Pharmaceutical Journal, 2023)
Antimicrobial peptides (AMPs) are small peptide molecules produced by a wide range of species, from bacteria to higher vertebrates, as a part of the innate immune system. These naturally produced peptides fight against intrusive microbes like viruses, bacteria, and fungi. AMPs are produced in various body parts by different organisms, such as skin secretion of amphibians; leaf, stem, fruits, or whole parts of plants; glandular secretion of mammals; the venom of reptiles and arthropods, etc. Due to this source variation, there is no universal method for the isolation, i.e., extraction and purification of the AMPs. Therefore, several techniques have been established to extract and purify these natural peptides from various sources. Generally, solid-phase extraction and chemical extraction techniques are the most common methods used for the extraction of AMPs. For purification and identification purposes, chromatography, gel electrophoresis, filtration, Edman degradation, circular dichroism, mass spectrometry, etc. are mainly adopted. In this review, we provide a brief discussion on the isolation process of AMPs based on their sources. This study would be helpful in isolating newer AMPs that could be used as potential antimicrobial agents. Bangladesh Pharmaceutical Journal 26(1): 99-111, 2023 (January)